Pub Talk: participation, education and men's health promotion - Francisco Nilson Paiva dos Santos; Vanessa Denardi Antoniassi Baldissera; Renata Ferraz de Toledo
ABSTRACT Objective: To evaluate the execution process of dialogical actions of a socio-educational group called "Pub Talk", created by professionals of the Paraisópolis II Basic Health Unit, recognizing challenges related to men's health. Method: Comprehensive evaluative research, which parameters were conceptual aspects of the Nola Pender's model. Interviews were conducted with the professionals and the focus group with men participating in the Group, analyzing three components of this model: individual experiences and characteristics; feelings and knowledge about the behavior one wants to achieve; desirable health promotion behavior. Results: The group is a self-care guiding intervention; values scientific and popular knowledge, with protagonism of those involved; covers the prevention of disease and changes of habits; has different perceptions regarding the structural and technical aspects of the meetings. Conclusion: Dialogic actions contributed to the promotion of the health of the participants by favoring the (re)cognition of determinants of their health and living conditions.